The Relationship between the Awareness and Performance of Parents Regarding Food Security with Anthropometric Indices among School-age Children in Bushehr, Iran, during 2017 - Zohre Kohansal; Niloofar Motamed; Saeid Najafpour Boushehri; Maryam Ravanipour (Mashhad University of Medical Sciences, 2019)
Parents' awareness and performance plays a key role in food safety of the children. This study aimed to investigate the relationship between parents' awareness and performance regarding food security with anthropometric indices in school-age children from Bushehr, Iran, during 2017. Data in this descriptive-analytical study was collected from 402 parents using questionnaires on awareness and performance as well as an anthropometric indices. According to the results, 313 parents had a good level of Food security awareness. Cereal consumption was insufficient in 70.4% of the children. 37.4% of the children were overweight or severely obese. Parents awareness and their performance revealed no significant relationship with children height and weight indices (P